0597 The Relationship Between Sleep Quality and Functional Outcomes Following Acute Stroke and Inpatient Rehabilitation. (25th May 2022) - Chen, Pin-Wei; O'Brien, Megan; Nguyen, Amy; Prokup, Sara; Knutson, Kristen; Yang, Hyun Sik; Hucker, Alejandro; Byron, Max; Goyal, Swati; Adcock, Emma; Morris, Linda; Mokhlesi, Babak; et al.
Abstract: Introduction: There is mounting evidence that sleep plays an important role in the rehabilitation and recovery process following acute stroke. Following acute care, many patients with stroke are admitted to inpatient rehabilitation facilities (IRFs), where they undergo intensive, interdisciplinary therapy to recover or relearn functional skills to minimize long-term disability. The role and impact of sleep in this early stage of stroke rehabilitation, however, is poorly understood. The purpose of this study is to investigate the relationship between sleep quality and clinical outcomes in the IRF setting following acute stroke. Methods: Patients wore a collection of wearable sensors to measure sleep and wake throughout their IRF stay. Linear mixed-effect models (LMEMs) were built to determine the relationship between functional outcomes and sleep quality. Independent variables were total sleep time (TST) and sleep efficiency (SE) derived from wearable sensors, calculated between two clinical measures. Dependent variables included scores from repeated measures of the 6-Minute Walk Test (6MWT), 10-Meter Walk Test (10MWT), Berg Balance Scale (BBS), and Action Research Arm Test (ARAT). Covariates included demographics such as age and stroke type. Results: Fifty-three individuals with stroke (age: 58.26±15.57 years; BMI: 28.27±6.16 kg/m2) consented to participate during their IRF program within 7 days of admission. All individuals were recruited from a single-site IRF between July 2020 and August 2021. The average length of stay was 17.85±6.99 days. There were no significant differences in TST between the first three nights and the last three nights (5.1±1.9 hours vs. 5.2±2.0 hours) or SE (67.8±17.7% vs. 69.0±17.8%). The greater standard deviation of TST was associated with lower 6MWT scores (R2=0.77, beta=−0.48, p=0.06), while the greater standard deviation of SE was associated with lower 10MWT scores (R2=0.80, beta=−0.20, p=0.18). Conclusion: Our preliminary findings indicate that greater variability in TST and SE are associated with walking endurance and mobility recovery. Future analyses will investigate additional measures of sleep and activity in IRF settings and their relationship with patient outcomes. This work can inform novel sleep interventions to optimize post-stroke recovery. Support (If Any): This work is supported by the Eunice Kennedy Shriver National Institute of Child Health & Human Development (NIH R01HD097786-01A1).